Immunoregulation by antigen-presenting cells in human intestinal lamina propria - Ogino, Takayuki; Takeda, Kiyoshi (Frontiers in Immunology, 2023)
Antigen-presenting cells, including macrophages and dendritic cells, are a type of innate immune cells that can induce the differentiation of T cells and activate the adaptive immune response. In recent years, diverse subsets of macrophages and dendritic cells have been identified in the intestinal lamina propria of mice and humans. These subsets contribute to the maintenance of intestinal tissue homeostasis by regulating the adaptive immune system and epithelial barrier function through interaction with intestinal bacteria. Further investigation of the roles of antigen-presenting cells localized in the intestinal tract may lead to the elucidation of inflammatory bowel disease pathology and the development of novel treatment approaches.